Use of laser scanner technology as part of the slope stability risk management strategy at Letšeng diamond mine - Lefu, N; Nokwe, V (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
The stability of slopes in open pit mines is an issue of great concern because of the detrimental consequences that instabilities can cause. Therefore, stringent systematic slope stability assessment and risk management are imperative to ensure the safe and continuous economic operation of these mines. Laser scanning technology is the most advanced method in geodesy and emerged as an indispensable tool in open pit data collection, interpretation and analysis. In 2018, Letšeng acquired a Maptek XR3 laser scanner for volumetric surveys, geological and geotechnical data collection and analysis, as well as tactical and strategic slope deformation monitoring. Letšeng diamond open pit mine is the highest altitude diamond mine in the world at around 3,100 m above sea level, where two kimberlite pipes are mined as successive pushbacks. The mine is in the northern region of Lesotho, within the Drakensberg Formation of the Karoo Supergroup. The article discusses the use of the laser scanning method as part of a slope stability management strategy at Letšeng. The first part discusses geological and geotechnical data collection, detailed structural analysis and detection of potentially unstable rock masses on the pit slope. The second part discusses slope reconciliation and slope deformation monitoring.
Keywords: laser scanning; slope stability; risk management